Incorporation of the autonomous liability of corporate bodies in the opinion on the new Criminal Code: do I need now a criminal compliance? - Ruiz Baltazar, Carmen (2015)
Currently, different legal systems are starting to demand criminal responsibility of corporate bodies. The Opinion on the New Criminal Code, prepared by the Justice and Human Rights Commission of the Congress of the Republic of Peru, follows this trend, proposing an exemption from liability in case the corporate body counts with a criminal compliance.Given this situation, in this article, the authors answer the arising questions: what does criminal compliance stands for? What are the accessory consequences of the criminal liability of corporate bodies in our current legislation? What are the novelties that the Opinion on the New Criminal Code introduces?